Research and Implementation of PLC Editor System - Qingchao Wei; Qizhong Cai; Congse Xie (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
According to the new type of portable PLC programming device adopting the own invention technology, a PLC editor system with ARM microprocessor and μC/OS-II system as the core was constructed. Logic operation instructions with multiple operands and their encodes were designed. The data storage capacity was expanded. A CAN extension protocol was formulated. Two-way chain table was adopted to edit PLC source instruction file dynamically, and the file was compiled to a binary object code file. According to CAN extension protocol format the object code file was encoded and sent to PLC host via CAN Bus. The results show that the system improves editing efficiency and the running speed of PLC host. Many sets of source instruction files’ storage, PLC source instruction file compiled accurately, the highly reliable communication and monitoring PLC host are implemented. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4424